Characterization of cDNAs encoding serine proteases and their transcriptional responses to Cry1Ab protoxin in the gut of Ostrinia nubilalis larvae - Yao, Jianxiu; Buschman, Lawrent L.; Oppert, Brenda; Khajuria, Chitvan; Zhu, Kun Yan (My University, 2012)
Serine proteases, such as trypsin and chymotrypsin, are the primary digestive enzymes in lepidopteran larvae, and are also involved in Bacillus thuringiensis (Bt) protoxin activation and protoxin/toxin degradation. We isolated and sequenced 34 cDNAs putatively encoding trypsins, chymotrypsins and their homologs from the European corn borer (Ostrinia nubilalis) larval gut. Our analyses of the cDNA-deduced amino acid sequences indicated that 12 were putative trypsins, 12 were putative chymotrypsins, and the remaining 10 were trypsin and chymotrypsin homologs that lack one or more conserved residues of typical trypsins and chymotrypsins. Reverse transcription PCR analysis indicated that all genes were highly expressed in gut tissues, but one group of phylogenetically-related trypsin genes, OnTry-G2, was highly expressed in larval foregut and midgut, whereas another group, OnTry-G3, was highly expressed in the midgut and hindgut. Real-time quantitative PCR analysis indicated that several trypsin genes (OnTry5 and OnTry6) were significantly up-regulated in the gut of third-instar larvae after feeding on Cry1Ab protoxin from 2 to 24 h, whereas one trypsin (OnTry2) was down-regulated at all time points. Four chymotrypsin and chymotrypsin homolog genes (OnCTP2, OnCTP5, OnCTP12 and OnCTP13) were upregulated at least 2-fold in the gut of the larvae after feeding on Cry1Ab protoxin for 24 h. Our data represent the first indepth study of gut transcripts encoding expanded families of protease genes in O. nubilalis larvae and demonstrate differential expression of protease genes that may be related to Cry1Ab intoxication and/or resistance.
Keywords: Ostrinia nubilalis; Serine proteases; cDNA; Cry1Ab protoxin